The effect of intensive care specialist on mortality in a Teaching Hospital in Turkey - İlkay Ceylan; Ebru Karakoç; İsa Kılıç (National Scientific Medical Center, 2021)
Aim: Specialization in critical care, which has a long history in various countries, is still developing in our country, and the practical outcomes of this relatively new discipline are yet to be not fully understood in our country. In the present study, we investigate the effect on mortality of the introduction of intensivists to a Level III closed intensive care unit. Material and methods: The study was launched after being granted approval by the ethics committee. In this retrospective study we included the patients who were treated in the same period in two consecutive years. We excluded who were under the age of 18 years, who stayed in the intensive care unit for less than 24 hours and postoperative patients. For the purpose of the study, the patients were divided into intensivist and pre-intensivist groups. Results: Aside from the shorter stay at the intensive care unit in intensivist group, mortality rate was lower in the pre-intensivist group, there was no statistically significant difference between the intensivist and pre-intensivist groups. Conclusion: Intensivists have positive effects on patients' clinical outcomes, although a change in even a single factor during the treatment of ICU patients does not be sufficient for a statistical difference.